Masjid Al-Falah Seoul as a Mosque-Based Social Safety Net for Muslim Diaspora Communities in South Korea - Abdurrahman, Muhammad Farhan; Thoha, Ahmad Faiz Khudlari; Mauludi, Mauludi (Islamic Management and Empowerment Journal, 2026)
Abstract This study examines how Masjid Al-Falah Seoul operates as a mosque-based social safety net for Muslim diaspora communities in South Korea. Using a qualitative single-case study, data were collected via semi-structured interviews, site observation, and document review with seven informants, including mosque leaders and congregants. Findings reveal that the mosque provides informal social protection through free meals (Geumbab), temporary accommodation, housing deposit support (Bojeunggeum), emergency assistance, and convert mentoring programs. These initiatives address economic, emotional, social, and spiritual needs, sustained through bonding, bridging, and linking social capital. The study demonstrates how religious institutions can strengthen community resilience and social cohesion, contributing to the literature on diaspora welfare and mosque-based social services. Keywords: mosque-based social services; Muslim diaspora; social safety net; social capital; informal welfare; South Korea